Serum insulin and leptin in patients with end stage renal disease on regular hemodialysis treatment (RDT) - Zaater, Mahmoud K (African Journal of Nephrology, 2023)
This work aimed to study serum insulin and serum leptin in patients with end stage renal disease on regular hemodialysis therapy. The study included two groups: Group I: 20 non diabetic, end stage renal disease male patients on regular hemodialysis therapy. Group II: 12 volunteers non-diabetic males as a control group, they were age and height matched, and of the same socioeconomic class as patients group. The results concluded that, patients with ESRD on RDT showed decrease in mean body mass index (BMI), significant reduction in mean serum insulin level and non significant increase in mean serum leptin level compared to the control group.